High-entropy alloy reinforced aluminum-based composite material and preparation method and application thereof
By introducing high-entropy alloy CoCrNiFeMo particles into aluminum-based composite materials and controlling the sintering conditions, a stable interface layer is formed, which solves the problem of insufficient hardness and wear resistance of aluminum-based composite materials, significantly improves its performance, and is suitable for applications in the field of friction.
Patent Information
- Application Number
- CN202411831766.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
The application of aluminum-based composite materials in the field of tribology is limited by their low intrinsic strength, limited hardness and wear resistance, making it difficult to meet the needs of lightweight and high performance.
By using high-entropy alloy CoCrNiFeMo particles as the reinforced phase, combined with the control of sintering temperature and pressure, a stable interface layer is formed to enhance the hardness and wear resistance of the aluminum matrix.
It has achieved the improvement of extremely high density, hardness, mechanical properties and wear resistance of aluminum-based composite materials, with an average friction coefficient of less than 0.56, which is suitable for applications in the friction field.
Smart Images

Figure CN119571140A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal matrix composite material preparation, and in particular to a high entropy alloy reinforced aluminum matrix composite material and a preparation method and application thereof. Background Art
[0002] The application background of aluminum-based composites in the field of tribology mainly stems from their excellent performance characteristics and wide industrial demand. With the development of science and technology, especially in the fields of aerospace, automobile and mechanical engineering, the demand for lightweight materials is increasing. In the field of tribology, they have good wear resistance and fatigue resistance. In friction contact, they can provide lower friction coefficient and higher wear resistance, extending the service life of components. Aluminum-based composites usually have good thermal conductivity, which helps to effectively dissipate heat during friction and reduce the degradation of material properties due to overheating.
[0003] In summary, the application background of aluminum-based composite materials in the field of tribology is driven by their superior physical and chemical properties and industrial needs. With the advancement of technology in the future, their application scope and effects are expected to be further expanded. However, the intrinsic strength of aluminum is low, and its hardness and wear resistance are limited. Based on this, there is an urgent need for an aluminum-based composite material with excellent wear resistance that has a simple preparation process and can be prepared at low cost to promote its application in the field of friction. Summary of the invention
[0004] To solve the above problems, the present invention provides a high entropy alloy reinforced aluminum-based composite material and a preparation method and application thereof, wherein high entropy alloy (CoCrNiFeMo) particles are used as a reinforcing phase, and the interface reaction relationship between the CoCrNiFeMo particles and the Al matrix is controlled by controlling the sintering temperature and pressure, so that a stable interface layer is formed between the CoCrNiFeMo particles and the Al matrix, which not only effectively solves the interface problem between the reinforcing phase and the matrix, but also enables the prepared aluminum-based composite material to have an extremely high density while greatly improving the hardness, mechanical properties and wear resistance of the composite material.
[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0006] A first aspect of the present invention provides a high entropy alloy reinforced aluminum-based composite material, comprising an aluminum matrix, high entropy alloy particles dispersed in the aluminum matrix, and an interface layer located between the aluminum matrix and the high entropy alloy particles.
[0007] Furthermore, the high entropy alloy is CoCrNiFeMo.
[0008] Furthermore, the mass percentage of the high entropy alloy in the high entropy alloy reinforced aluminum-based composite material is preferably 2%-6%.
[0009] Furthermore, the particle size of the high entropy alloy particles is 15-65 μm; and the thickness of the interface layer is 3-6 μm.
[0010] Furthermore, the average friction coefficient of the high entropy alloy reinforced aluminum-based composite material is less than 0.56.
[0011] The second aspect of the present invention provides a method for preparing the high entropy alloy reinforced aluminum-based composite material according to the first aspect, comprising the following steps:
[0012] (1) ball-milling high entropy alloy powder and aluminum powder to obtain pre-sintered powder;
[0013] (2) placing the pre-sintered powder prepared in step (1) in a mold for cold pressing under a protective atmosphere to obtain a green body;
[0014] (3) subjecting the green body prepared in step (2) to rapid hot pressing and sintering to obtain the high entropy alloy reinforced aluminum-based composite material.
[0015] Furthermore, the protective atmosphere is preferably argon and / or nitrogen, and other inert gases may also be used.
[0016] Furthermore, in step (1), the high entropy alloy particles are preferably spherical or nearly spherical particles.
[0017] Furthermore, in step (1), the average particle size of the high entropy alloy particles is preferably 15-53 μm.
[0018] Furthermore, in step (1), the average particle size of the aluminum powder is preferably 5-20 μm.
[0019] Furthermore, in step (1), the mass ratio of the high entropy alloy powder to the pre-sintered powder is (0.02-0.04):1, for example, 0.02:1, 0.025:1, 0.03:1, 0.04:1, etc., including but not limited to the mass ratios listed above.
[0020] Furthermore, in step (1), in the step of ball milling and mixing, the ball-to-material ratio is preferably (5-10):1, the ball milling speed is preferably 200-400 rpm, and the ball milling time is preferably 4-8 h; in some preferred embodiments, the powder after ball milling and mixing is subjected to vacuum drying to obtain the pre-sintered powder; in the vacuum drying step, the vacuum degree is 2.0×10 -2 -1.0×10 -2 pa, temperature is 50-80℃, and drying time is 2-6h.
[0021] Furthermore, in step (2), the mold comprises a graphite mold.
[0022] Furthermore, in step (2), in the cold press forming step: the pressure is preferably 50 MPa-80 MPa, and the holding time is preferably 2-6 h.
[0023] Furthermore, in step (3), the rapid hot pressing sintering treatment is specifically as follows: placing a mold containing the green body in a sintering furnace cavity, evacuating the cavity and maintaining the hydraulic pressure at 30 MPa-50 MPa, then heating the cavity to 450-550°C for 5-10 min, maintaining the pressure and cooling the cavity to below 60°C to obtain the high entropy alloy reinforced aluminum-based composite material.
[0024] Preferably, the vacuum degree of the sintering furnace cavity after evacuation is 1.0×10 -2 -1.0×10 -1 Pa.
[0025] In some preferred embodiments, the temperature rise treatment is specifically as follows: turning on the DC power supply, controlling the current to be between 2000A and 4000A, the voltage to be between 2V and 6V, and performing the temperature rise treatment at a temperature rise rate of between 80°C and 150°C / min.
[0026] The third aspect of the present invention provides an application of the high entropy alloy reinforced aluminum-based composite material described in the first aspect or the high entropy alloy reinforced aluminum-based composite material prepared by the preparation method described in the second aspect in the field of friction.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a high entropy alloy reinforced aluminum-based composite material, which uses high entropy alloy particles as a reinforcement phase, and generates a reaction layer through diffusion between the high entropy alloy particles and an Al matrix. The reaction layer becomes a link between the hard particle high entropy alloy and the soft Al matrix, and effectively solves the interface problem between the reinforcement phase and the Al matrix. The prepared aluminum-based composite material has an extremely high density, and at the same time, the hardness, mechanical properties and wear resistance of the composite material are greatly improved, and the average friction coefficient is less than 0.56, which has good application prospects in the field of friction.
[0029] The present invention also provides a method for preparing the above-mentioned high entropy alloy reinforced aluminum-based composite material, which can be prepared by simple ball milling, cold pressing, and rapid hot pressing and sintering. The preparation process is simple, easy to operate and low in cost. In addition, a controllable interface reaction layer can be obtained by controlling the reaction temperature, which can not only ensure the interface performance of the high entropy alloy particles and the Al matrix, but also ensure that the high strength of the high entropy alloy particles is retained inside the particles. The process has strong controllability, is suitable for industrial mass production, and is conducive to practical applications in the field of friction. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM morphology of the CoCrNiFeMo / Al composite material prepared in Example 1.
[0031] Figure 2 This is the SEM morphology of the CoCrNiFeMo / Al composite material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0034] Example 1
[0035] This embodiment provides a high entropy alloy reinforced aluminum-based composite material, and the preparation process thereof is as follows:
[0036] (1) In a vacuum glove box, the glove box was filled with an inert gas - high-purity argon. A precision electronic balance was used to weigh 0.60 g of CoCrNiFeMo powder (accounting for 2.0%) and 29.40 g of Al powder in a vacuum ball mill. Stainless steel balls were placed in a vacuum ball mill. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 300 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h for drying. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0037] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0038] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5 tons, then start the equipment to evacuate the mold. When the vacuum reaches 1.0×10 -2 Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After the temperature was raised to 550℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold was cooled to 60℃ and the sample was taken out. The CoCrNiFeMo / Al composite material was obtained.
[0039] Figure 1 This is a metallographic SEM image of the CoCrNiFeMo / Al composite material prepared in this embodiment. As can be seen from the figure, the CoCrNiFeMo and Al matrix have a clear boundary line and a very uniform core-shell structure is obtained. It can be seen from the figure that the composition of the dark area in the center is determined to be CoCrNiFeMo particles, and the composition of the outermost light area is determined to be Al. It is precisely because of the existence of this reaction layer that the foundation is laid for improving the mechanical properties and wear resistance of the composite material.
[0040] Example 2
[0041] This embodiment provides a high entropy alloy reinforced aluminum-based composite material, which is mainly different from Embodiment 1 in that the mass proportion of CoCrNiFeMo powder, ball milling parameters and sintering temperature are as follows:
[0042] (1) In a vacuum glove box, the glove box was filled with an inert gas - high-purity argon. A precision electronic balance was used to weigh 1.20 g of CoCrNiFeMo powder (accounting for 4%) and 28.80 g of Al powder in a vacuum ball mill. Stainless steel balls were placed in a vacuum milling jar. The ball-to-material ratio was 10:1, and the mass ratio of 10 mm diameter to 6 mm diameter was 1:1. The ball milling time was 5 h, and the rotation speed of the planetary ball mill was 400 r / min. After the ball milling, the mixed powder was placed in an environment at 50 °C for 4 h for drying. The vacuum degree of the drying oven was 1.0 × 10 -2 pa. After vacuum drying, the pre-sintered powder can be obtained.
[0043] (2) Place the prepared pre-sintered powder and graphite mold together in a glove box and introduce high-purity argon gas to protect the powder from contact with moisture in the air to prevent oxidation and moisture. First, load the powder into the graphite mold and press the powder with graphite pressure heads at both ends. Since the graphite mold can only withstand limited pressure, the cold pressing pressure is controlled to 50 MPa. After maintaining the pressure for 5 hours, take out the mold containing the pre-sintered powder.
[0044] (3) Place the cold pressed mold in a rapid hot pressing sintering furnace, start the hydraulic system first, keep the pressure at 0.5t, then start the equipment to evacuate. When the vacuum reaches 1.0×10 -2 Pa, the pressure began to increase, and the pressure was maintained at 50MPa. At this time, the DC power supply was turned on, and the current and voltage were controlled by the program, and the heating rate was maintained at 100℃ / min. After heating to 450℃, the temperature and pressure were maintained for 10min. After the insulation was completed, the DC power supply was turned off, and the pressure was maintained until the mold cooled to 60℃ and the sample was taken out. The CoCrNiFeMo / Al composite material was obtained.
[0045] Comparative Example 1
[0046] This comparative example provides a high entropy alloy reinforced aluminum-based composite material, which is different from Example 1 only in that the sintering temperature is lowered to 400° C., and the other operations are the same to prepare the corresponding CoCrNiFeMo / Al composite material.
[0047] Figure 2 This is the metallographic SEM morphology of the CoCrNiFeMo / Al composite material prepared in Comparative Example 1. It can be seen from the figure that when the preparation temperature is reduced to 400°C, there is basically no diffusion reaction at the interface between the CoCrNiFeMo particles and the Al matrix, which is only a simple mechanical bond, and no metallurgical bonding occurs, and no reaction layer appears. The pores around the particles are more distributed, and there are defects in the Al matrix, which is not dense.
[0048] Performance Testing
[0049] The composite materials or aluminum materials prepared in the above embodiments and comparative examples were tested for density, microhardness, ultimate tensile strength, average friction coefficient and wear rate, wherein:
[0050] Density: It is the ratio of actual density to theoretical density, used to characterize the density of materials;
[0051] Microhardness test: Shanghai Hengyi EM500-1A microhardness tester was used, with a loading force of 100 gf and a holding time of 15 s;
[0052] Ultimate tensile strength test: using Instron 34FM-100 electronic universal material testing machine, the tensile speed is 0.1mm / min;
[0053] Average friction coefficient test: measured using Rtec-MFT-5000-H multifunctional friction and wear testing machine, with an applied load of 30N, a reciprocating friction speed of 0.05m / s, and a grinding material of GCr15;
[0054] Wear volume test: The wear volume was measured by ZEISS LSM-700 laser confocal microscope, and then the wear volume was calculated.
[0055] The test results are summarized in Table 1
[0056] Table 1
[0057]
[0058]
[0059] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A high entropy alloy reinforced aluminum-based composite material, characterized in that: The composite material comprises an aluminum matrix and high entropy alloy particles, wherein the high entropy alloy particles are dispersed in the aluminum matrix, and a diffusion interface layer is provided between the aluminum matrix and the high entropy alloy particles.
2. The high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The high entropy alloy is CoCrNiFeMo alloy.
3. The high entropy alloy reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The mass percentage of the high entropy alloy in the high entropy alloy reinforced aluminum-based composite material is 2%-6%.
4. The high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The particle size of the high entropy alloy particles is 15-65 μm; the thickness of the interface layer is 3-6 μm.
5. The method for preparing a high entropy alloy reinforced aluminum-based composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: under a protective atmosphere, (1) ball-milling high entropy alloy powder and aluminum powder to obtain pre-sintered powder; (2) placing the pre-sintered powder prepared in step (1) in a mold for cold pressing to obtain a green body; (3) subjecting the green body prepared in step (2) to rapid hot pressing and sintering to obtain the high entropy alloy reinforced aluminum-based composite material.
6. The method for preparing a high entropy alloy reinforced aluminum-based composite material according to claim 5, characterized in that: In step (1), at least one of the following features is included: (1) The high entropy alloy particles are spherical or nearly spherical particles; (2) The average particle size of the high entropy alloy particles is 15-45 μm; (3) The average particle size of the aluminum powder is 5-20 μm; (4) The mass ratio of the high entropy alloy powder to the pre-sintered powder is (0.02-0.04):
1.
7. The preparation method according to claim 5, characterized in that: In step (1), in the ball milling mixing step, the ball-to-material ratio is (5-10):1, the ball milling speed is 200-400 rpm, and the ball milling time is 4-8 hours; Preferably, the powder after ball milling and mixing is vacuum dried to obtain the pre-sintered powder; in the vacuum drying step: the vacuum degree is 2.0×10 -2 -1.0×10 -2 pa, temperature is 50-80℃, and drying time is 2-6h.
8. The preparation method according to claim 5, characterized in that: In step (2), the mold includes a graphite mold; in the cold pressing step: the pressure is 50MPa-80MPa, and the holding time is 4-6h.
9. The preparation method according to claim 5, characterized in that: In step (3), the rapid hot pressing sintering treatment is specifically as follows: placing a mold containing the green body in a sintering furnace cavity, evacuating and maintaining a hydraulic pressure of 30 MPa-50 MPa, and then heating the temperature to 450-550° C. and keeping the temperature for 5-8 min, maintaining the pressure and cooling the temperature to below 60° C. to obtain the high entropy alloy reinforced aluminum-based composite material; Preferably, the vacuum degree of the sintering furnace cavity after evacuation is 1.0×10 -2 -1.0×10 -1 Pa; The temperature rise treatment is specifically as follows: turn on the DC power supply, control the current to be between 2000A and 4000A, the voltage to be between 2V and 6V, and perform the temperature rise treatment at a temperature rise rate of between 80°C and 150°C / min.
10. Use of the high entropy alloy reinforced aluminum-based composite material according to any one of claims 1 to 4 in the field of friction.
Citation Information
Cited By
Reduced graphene oxide / high-entropy alloy reinforced aluminum alloy bar and preparation method thereof
CN120174228A